Indian capital market analysis 2020 year end and 2021 year beginning - Govindasamy, Dr.P.; Shankar, Dr.Kapila Uma; Ravimohan, Mr.R. (The journal of contemporary issues in business and government, 2021)
Due to Covid-19 the Indian economy continuously given shock and halt of operations deteriorates its performance considerably and makes the lives harm in many ways. In order to view this situation through Indian capital market, it is directed through this review of capital market information. This study systematically takes views the data by analyzing the fund mobilization, secondary market operations, and Indian depository and derivatives segments in details. This review considers the data set in Dec-2020 and Jan-2021 being the year end and year beginning focus.